ANALYSIS OF THE LEVEL OF COASTAL COMMUNITY WELFARE IN SEILAUT LAUT, ASAHAN REGENCY - Malawat, Saleh (Asosiasi Dosen Akuntansi Indonesia, 2021)
The purpose of this study was to determine the level of welfare of coastal communities in Seilautlaut, Asahan Regency using primary data for 79 respondents representing the entire population of the coastal communities in the District of Silautlaut, Asahan. The data was collected using questionnaires. The analysis method used is descriptive qualitative. The data collected was processed and presented in the form of tables. The results showed that the coastal communities in the district of Silautlaut Asahan generally have a relatively low level of prosperity or poverty. This is indicated by the low levels of income and household spending substantial and living conditions are not feasible.